(untitled) (GAIMS Journal of Medical Sciences, 2023)
INTRODUCTION: Urinary tract infection is the 2ndmost common hospital- acquired infection and recognized as a significant problem in diabetic patients. UTI increases morbidity in diabetic patients because sugar serves as the growth medium for uropathogens. Complications due to UTIs are more in diabetics compared to non-diabetic patients. AIMS AND OBJECTIVES: To detect uropathogens and their antibiotic susceptibility pattern in Urinary Tract Infections in diabetic and non-diabetic patients. MATERIAL AND METHOD: The retrospective study was conducted from June 2022 to August 2022 in 136 diabetic and 101 non-diabetic patients having culture positive for urinary tract infection. Urine samples were cultured and examined for bacterial growth by various microbiological methods. After the identification of the bacterial pathogen, antimicrobial susceptibility testing was done on Muller Hinton agar according to CLSI guidelines. RESULTS: A total of 237 culture-positive patients of UTI were studied, 136(57.4%) were diabetics and 101(42.6%) were non-diabetics. Escherichia coli was the most common isolated organism in diabetics(63.9%) and non-diabetics(66.4%), followed by Klebsiella pneumoniae in diabetics(15.4%) and non-diabetics(15.9%). There were no significant differences in the prevalence of Pseudomonas aeruginosa, Acinetobacter baumannii, Staphylococcus aureus, and Enterococcus spp., in both groups. No significant difference in the antibiotic sensitivity pattern of both groups. CONCLUSION: The prevalence of UTIs were high in diabetics than non- diabetics. In both groups, E.coli was the most common organism followed by Klebsiella. E.coli from diabetics and non-diabetics have demonstrated higher resistance to cephalosporins and sensitivity to Nitrofurantoin, Sparfloxacin, Piperacillin-Tazobactam, Imipenam and Gatifloxacin.